Light on life: immunoscore immune-checkpoint, a predictor of immunotherapy response - Assia Hijazi; Carlotta Antoniotti; Chiara Cremolini; Jérôme Galon (OncoImmunology, 2023)
In the last decade, a plethora of immunotherapeutic strategies have been designed to modulate the tumor immune microenvironment. In particular, immune checkpoint (IC) blockade therapies present the most promising advances made in cancer treatment in recent years. In non-small cell lung cancer (NSCLC), biomarkers predicting response to IC treatments are currently lacking. We have recently identified Immunoscore-IC, a powerful biomarker that predicts the efficiency of immune-checkpoint inhibitors (ICIs) in NSCLC patients. Immunoscore-IC is an in vitro diagnostic assay that quantifies densities of PD-L1+, CD8+ cells, and distances between CD8+ and PD-L1+ cells in the tumor microenvironment. Immunoscore-IC can classify responder vs non-responder NSCLC patients for ICIs therapy and is revealed as a promising predictive marker of response to anti-PD-1/PD-L1 immunotherapy in these patients. Immunoscore-IC has also shown a significant predictive value, superior to the currently used PD-L1 marker. In colorectal cancer (CRC), the addition of atezolizumab to first-line FOLFOXIRI plus bevacizumab improved progression-free survival (PFS) in patients with previously untreated metastatic CRC. In the AtezoTRIBE trial, Immunoscore-IC emerged as the first biomarker with robust predictive value in stratifying pMMR metastatic CRC patients who critically benefit from checkpoint inhibitors. Thus, Immunoscore-IC could be a universal biomarker to predict response to PD-1/PD-L1 checkpoint inhibitor immunotherapy across multiple cancer indications. Therefore, cancer patient stratification (by Immunoscore-IC), based on the presence of T lymphocytes and PD-L1 potentially provides support for clinicians to guide them through combination cancer treatment decisions.